Systematic literature review of templates for reporting prehospital major incident medical management. Issue 8 (1st August 2013) - Fattah, Sabina; Rehn, Marius; Reierth, Eirik; Wisborg, Torben
Abstract : Objective: To identify and describe the content of templates for reporting prehospital major incident medical management. Design: Systematic literature review according to PRISMA guidelines. Data sources: PubMed/MEDLINE, EMBASE, CINAHL, Scopus and Web of Knowledge. Grey literature was also searched. Eligibility criteria for selected studies: Templates published after 1 January 1990 and up to 19 March 2012. Non-English language literature, except Scandinavian; literature without an available abstract; and literature reporting only psychological aspects were excluded. Results: The main database search identified 8497 articles, among which 8389 were excluded based on title and abstract. An additional 96 were excluded based on the full-text. The remaining 12 articles were included in the analysis. A total of 107 articles were identified in the grey literature and excluded. The reference lists for the included articles identified five additional articles. A relevant article published after completing the search was also included. In the 18 articles included in the study, 10 different templates or sets of data are described: 2 methodologies for assessing major incident responses, 3 templates intended for reporting from exercises, 2 guidelines for reporting in medical journals, 2 analyses of previous disasters and 1 Utstein-style template. Conclusions: More than one template exists for generating reports. The limitations of the existing templates involve internal and external validity, and none of them have been tested for feasibility in real-life incidents. Trial registration: The review is registered in PROSPERO (registration number: CRD42012002051).